Coping resources of heart failure patients: a comparison with cancer patients and individuals having no chronic condition results from the esther study - Paul, Cinara; Loßnitzer, Nicole; Böhlen, Friederike; Haefeli, Walter E.; Holleczek, Bernd; Brenner, Hermann; Schöttker, Ben; Wild, Beate (Heart & lung, 2020)
Background - Heart failure (HF) and cancer patients share similarities in symptom burden and depression prevalence. Coping resources, such as optimism have been associated with improved health-related quality of life (HRQoL) and mental health. - Objectives - To investigate a wide range of resources in a large population-based sample of HF patients; to compare resources between three groups: HF patients, cancer patients, and individuals having no chronic condition. - Methods - This cross-sectional analysis was performed among n = 2761 subjects who participated in home visits during the 11-year follow-up of the epidemiological ESTHER study. Resources were assessed by trained medical doctors through a questionnaire that lists 26 items. One-way analyses of covariance (ANCOVAs) controlled for sociodemographic variables and depression were performed to compare resources between groups. - Results - Family and self-efficacy were the most frequently reported resources in all groups. HF patients reported optimism significantly less frequently as a resource in comparison to cancer patients (p=.031). HF patients showed significantly lower levels of resource factor 3 (positive attitude), compared to cancer patients (p=.006), and not chronically ill participants (p=.037). - Conclusions - Family and self-efficacy seem to be the most important resources, regardless of diagnosis. HF patients appear to have significantly lower levels of resources concerning positive attitude, compared to cancer patients, and not chronically ill individuals. We suggest the development of psychosocial interventions to enhance optimism in HF.
Gesehen am 09.02.2021